Sustainable nanocomposites in food packaging - Anuar, Hazleen; Ali, Fathilah; Buys, Yose Fachmi; Mohd Apandi, Siti Nur E'zzati; Abd. Rashid, Siti Munirah Salimah; Adli, Sarah Amalina (Springer Nature Switzerland, 2019)
Human activities have already brought about changes to the ecological system worldwide, thereby giving rise to global warming and pollution. These problems have led to increased environmental degradation, which is destroying many things. Many plastic packaging industries are trying to minimize their reliance on synthetic materials in order to reduce toxicity levels [47]. Therefore, new environmental guidelines are forcing the exploration of novel packaging materials that are compatible with the environment. Such materials are currently being developed from various natural resources, among which biopolymers are the most popular. Biopolymers have many advantages compared to petroleum-based plastics in terms of performance, processability, and biodegradability [82]. There are several types of biopolymer matrices including polylactic acid (PLA), polyvinyl alcohol (PVA), polyhydroxy butyrate (PHB) and starch-based polymers. The poor gas and water barrier properties, unstable mechanical properties and weak resistivity of plastics have limited their use in various applications [55]. Therefore, to improve their mechanical and barrier properties, and to impart novel features to them, biopolymers are reinforced with various nanofillers for the development of nanocomposites.